(untitled) (AYUSHDHARA, 2022)
Jeevanti is the drug having Rasayana, Jeevaniya/ vitalizer, Vaya Sthaapana, Vrishya, Stanyajanana, Balya, and Anulomana properties. Acharya Charaka on the basis of its pharmacological action, and categorized under Jeevaniya Gana, Madhura Skandha, vayasthapana, etc. Acharya Vaghbhata has clarified its uses during pregnancy in Garbhini Paricharya. Ayurveda, Vedic science considered this state as Garbhini and various Acharyas has given their very own rituals known as Garbhini Paricharya. It has been practiced and tested from century which deals with the both maternal and fetal wellbeing but evidence is the most important fact for today’s era, hence, various drugs are being studied to know their efficacy and safety during pregnancy. Rasayana drugs have health restorative action which prevents Garbhini and Garbha from various infections and other complications. As well as, it improves strength of fetus by improving fetal nourishment through proper formation of Rasa dhatu. This conceptual study will put limelight on the importance of Rasayana drug i.e., Jeevanti in Garbhini Paricharya along with its benefits to Fetal nourishment and maternal wellbeing.